A Case of Presumed Bonsai-induced Severe Toxic Optic Neuropathy. (2nd January 2022) - Yasar, Erdogan; Tomac, Hatice Suhan; Gurlevik, Ugur
ABSTRACT: Apart from the known factors that cause toxic optic neuropathy, there may be factors that have not yet been identified. We report a 32-year-old man who presented with a complaint of decreased vision. His optic discs were diffusely covered with a black pigment, and below were atrophic. The vessels appeared to have disappeared below the pigmentation. He reported smoking tobacco, drinking alcohol, and using cannabis. His vision in both eyes began decreasing gradually after he started using bonsai, a synthetic cannabinoid, 2 years previously. No case of toxic optic neuropathy with bilateral severe vision loss and intense pigmentation with the use of bonsai has been reported before, and our case will be reinforced if other such cases are reported in the future.